Thermally conductive silicone composition, semiconductor device and method for manufacturing the same
By using silver powder and spherical silver powder with specific tap density, special surface area and particle size distribution in thermally conductive silica gel, the problem of thermal resistance deterioration when the thickness exceeds the minimum compression thickness is solved, and effective heat dissipation of high-heat-generating integrated circuit components is achieved.
Patent Information
- Application Number
- JP2023531878
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-07-02
- Filing Date
- 2022-06-23
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-06-23
AI Technical Summary
When the thickness of existing thermally conductive materials and thermally conductive silicones exceeds the minimum compression thickness (BLT), the thermal resistance will deteriorate, resulting in poor heat dissipation effect on high-heat generated integrated circuit components such as CPUs.
The thermal conductivity silicone composition mixed with silver powder and spherical silver powder in specific tissue polysiloxanes is used to improve thermal conductivity by controlling the tap density, special surface area and particle size distribution of the silver powder.
It realizes that the thermal conductivity is maintained when the thickness exceeds the minimum compression thickness (BLT), effectively improving the heat dissipation effect of high-heat generation integrated circuit components.
Smart Images

Figure 0007650612000007 
Figure 0007650612000001 
Figure 0007650612000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a silicone composition having excellent thermal conductivity, a semiconductor device, and a method for producing the same. [Background technology]
[0002] Many electronic components generate heat during use, and in order for them to function properly, it is necessary to remove the heat from the electronic components. In particular, integrated circuit elements such as CPUs used in personal computers are generating more heat due to faster operating frequencies, making heat countermeasures an important issue. To solve this problem, many methods have been proposed as a means of removing heat. In particular, for electronic components that generate a lot of heat, a method has been proposed in which a thermally conductive material such as thermally conductive grease or a thermally conductive sheet is placed between the electronic component and a member such as a heat sink to release the heat.
[0003] Japanese Patent Laid-Open No. 2-153995 (Patent Document 1) discloses a silicone grease composition in which spherical hexagonal aluminum nitride powder of a certain particle size range is blended with a specific organopolysiloxane, Japanese Patent Laid-Open No. 3-14873 (Patent Document 2) discloses a thermally conductive silicone grease that combines aluminum nitride powder with fine particle size and aluminum nitride powder with coarse particle size, Japanese Patent Laid-Open No. 10-110179 (Patent Document 3) discloses a thermally conductive silicone grease that combines aluminum nitride powder and zinc oxide powder, and Japanese Patent Laid-Open No. 2000-63872 (Patent Document 4) discloses a thermally conductive grease composition that uses aluminum nitride powder that has been surface-treated with organosilane. The thermal conductivity of aluminum nitride is 70 to 270 W / mK, and a material with higher thermal conductivity than this is diamond, which has a thermal conductivity of 900 to 2,000 W / mK. Japanese Patent Laid-Open Publication No. 2002-30217 (Patent Document 5) discloses a thermally conductive silicone composition in which diamond, zinc oxide, and a dispersant are added to a silicone resin. Furthermore, Japanese Patent Laid-Open No. 2000-63873 (Patent Document 6) and Japanese Patent Laid-Open No. 2008-222776 (Patent Document 7) disclose thermally conductive grease compositions in which a base oil such as silicone oil is mixed with metallic aluminum powder. Furthermore, Japanese Patent No. 3130193 (Patent Document 8) and Japanese Patent No. 3677671 (Patent Document 9) disclose the use of silver powder with high thermal conductivity as a filler. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 2-153995 [Patent Document 2] Japanese Patent Application Publication No. 3-14873 [Patent Document 3] Japanese Patent Application Publication No. 10-110179 [Patent Document 4] JP 2000-63872 A [Patent Document 5] JP 2002-30217 A [Patent Document 6] JP 2000-63873 A [Patent Document 7] JP 2008-222776 A [Patent Document 8] Patent No. 3130193 [Patent Document 9] Patent No. 3677671 Summary of the Invention [Problem to be solved by the invention]
[0005] When thermally conductive materials or thermally conductive greases are applied to areas that are thicker than their minimum compression thickness (BLT), there is a problem that the thermal resistance deteriorates. Therefore, there is a demand for thermally conductive materials that have a sufficient heat dissipation effect against the heat generated by integrated circuit elements such as modern CPUs, even when applied to areas that are thicker than their minimum compression thickness (BLT). Therefore, an object of the present invention is to provide a thermally conductive silicone composition that exhibits good heat dissipation properties. [Means for solving the problem]
[0006] As a result of intensive research conducted by the present inventors in order to achieve the above-mentioned object, they discovered that a composition in which silver powder having a specific tap density, specific surface area, and aspect ratio, and spherical silver powder of a specific particle size are mixed into a specific organopolysiloxane, results in a cured product having extremely excellent thermal conductivity, and thus completed the present invention. That is, the present invention provides the following thermally conductive silicone composition, etc.
[0007] <1> A thermally conductive silicone composition comprising the following components (A), (B), (C), (D), and (E): (A) Kinematic viscosity at 25°C is 10 to 100,000 mm 2 / s, and containing at least two alkenyl groups bonded to silicon atoms in each molecule: 100 parts by mass (B) Organohydrogenpolysiloxane containing at least two hydrogen atoms bonded to silicon atoms (SiH groups) per molecule: an amount such that the number of hydrogen atoms bonded to silicon atoms in component (B) is 0.8 to 6 per alkenyl group in the entire composition. (C) a catalyst for hydrosilylation reaction: an effective amount (D) Tap density is 3.0 g / cm 3 and the specific surface area is 2.0m or more. 2 / g or less and an aspect ratio of 2.0 to 50: 500 to 3,000 parts by mass (E) The average particle size is 0.5 to 100 μm and the tap density is 4.0 g / cm 3 and the specific surface area is 1.5m or more. 2 / g or less and an aspect ratio of less than 2.0: 500 to 3,000 parts by mass <2> The ratio α / β of the mass α of component (D) to the mass β of component (E) is 0.1 to 6. <1> 2. The thermally conductive silicone composition according to claim 1 . <3> <1> or <2> 2. A cured product of the thermally conductive silicone composition according to claim 1. <4> A semiconductor device comprising a heat-generating electronic component and a heat sink, <3> 2. A semiconductor device comprising a cured product of the thermally conductive silicone composition according to claim 1 interposed therebetween. <5> <1> or <2> 1. A method for producing a semiconductor device, comprising the step of heating the thermally conductive silicone composition according to claim 1 to 80° C. or higher while applying a pressure of 0.01 MPa or more between a heat-generating electronic component and a heat sink. Effect of the Invention
[0008] The cured product of the thermally conductive silicone composition of the present invention has excellent thermal conductivity and is therefore useful in semiconductor devices. [Brief description of the drawings]
[0009] [Figure 1] 1 is a schematic vertical sectional view showing an example of a semiconductor device of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The thermally conductive silicone composition of the present invention will now be described in detail.
[0011] Component (A) The organopolysiloxane of component (A) is the base polymer of the composition of the present invention and contains at least two alkenyl groups bonded to silicon atoms in each molecule. The molecular structure of component (A) can be, for example, a straight-chain structure or a cyclic structure, and these structures may be branched. However, straight-chain diorganopolysiloxanes in which the main chain is basically composed of repeating diorganosiloxane units and both molecular chain terminals are blocked with triorganosiloxy groups are preferred.
[0012] The kinetic viscosity of component (A) at 25°C is 10 to 100,000 mm 2 / s, 100~50,000mm 2 / s is preferable. 2 If it is smaller than 100,000mm / s, oil bleeding will occur easily when it is mixed into the composition. 2 If it is greater than 1 / s, the absolute viscosity of the composition when it is incorporated into the composition will be high, resulting in poor handleability. Note that the kinematic viscosity of the organopolysiloxane of component (A) described in this specification is the value at 25°C measured with an Ostwald viscometer.
[0013] Examples of alkenyl groups bonded to silicon atoms in component (A) include vinyl groups, allyl groups, butenyl groups, pentenyl groups, hexenyl groups, heptenyl groups, etc., which preferably have 2 to 8 carbon atoms, more preferably 2 to 4 carbon atoms, with vinyl groups being particularly preferred. When the organopolysiloxane of component (A) has a linear structure, it is sufficient for each molecule to contain two or more alkenyl groups bonded to silicon atoms, and the alkenyl groups may be bonded to silicon atoms only at either the molecular chain terminals or at parts other than the molecular chain terminals, or both.
[0014] Examples of organic groups other than alkenyl groups that are bonded to silicon atoms in component (A) include unsubstituted or halogen-substituted monovalent hydrocarbon groups such as alkyl groups, particularly alkyl groups having 1 to 10 carbon atoms, such as methyl, ethyl, propyl, butyl, pentyl, hexyl, cyclohexyl, and heptyl; aryl groups, particularly aryl groups having 6 to 14 carbon atoms, such as phenyl, tolyl, xylyl, and naphthyl; aralkyl groups, particularly aralkyl groups having 7 to 14 carbon atoms, such as benzyl and phenethyl; and halogenated alkyl groups, particularly halogenated alkyl groups having 1 to 3 carbon atoms, such as chloromethyl, 3-chloropropyl, and 3,3,3-trifluoropropyl. Methyl and phenyl groups are particularly preferred.
[0015] Specific examples of component (A) include dimethylsiloxane-methylvinylsiloxane copolymers capped at both molecular chain terminals with trimethylsiloxy groups, methylvinylpolysiloxanes capped at both molecular chain terminals with trimethylsiloxy groups, dimethylsiloxane-methylvinylsiloxane-methylphenylsiloxane copolymers capped at both molecular chain terminals with trimethylsiloxy groups, dimethylpolysiloxanes capped at both molecular chain terminals with dimethylvinylsiloxy groups, methylvinylpolysiloxanes capped at both molecular chain terminals with dimethylvinylsiloxy groups, dimethylsiloxane-methylvinylsiloxane copolymers capped at both molecular chain terminals with dimethylvinylsiloxy groups, dimethylsiloxane-methylvinylsiloxane-methylphenylsiloxane copolymers capped at both molecular chain terminals with dimethylvinylsiloxy groups, dimethylsiloxane-methylvinylsiloxane-methylphenylsiloxane copolymers capped at both molecular chain terminals with dimethylvinylsiloxy groups, dimethylpolysiloxanes capped at both molecular chain terminals with trivinylsiloxy groups, 1 3SiO 0.5 (R 1 is an unsubstituted or substituted monovalent hydrocarbon group other than an alkenyl group. The same applies below.) and a siloxane unit represented by the formula: R 1 2R 2 SiO 0.5 (R 2 is an alkenyl group. The same applies below.) and a siloxane unit represented by the formula: R 1 Organopolysiloxane copolymers consisting of units represented by the formula: 2SiO and siloxane units represented by the formula: SiO2, 1 3SiO 0.5Siloxane units represented by the formula: R 1 2R 2 SiO 0.5 and an organopolysiloxane copolymer having a siloxane unit represented by the formula: SiO2, 1 2R 2 SiO 0.5 Siloxane units represented by the formula: R 1 Organopolysiloxane copolymers consisting of siloxane units represented by the formula: SiO2 and siloxane units represented by the formula: R 1 R 2 Siloxane units represented by SiO and the formula: R 1 SiO 1.5 Siloxane units or formula: R 2 SiO 1.5 and organopolysiloxane copolymers comprising siloxane units represented by the following formula: These components (A) can be used singly or in combination of two or more.
[0016] R in the above formula 1 Examples of the alkyl groups include alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, and heptyl; aryl groups such as phenyl, tolyl, xylyl, and naphthyl; aralkyl groups such as benzyl and phenethyl; and halogenated alkyl groups such as chloromethyl, 3-chloropropyl, and 3,3,3-trifluoropropyl. 2 Examples of the alkyl group include a vinyl group, an allyl group, a butenyl group, a pentenyl group, a hexenyl group, and a heptenyl group.
[0017] (B) Component The organohydrogenpolysiloxane of component (B) is not particularly limited as long as it has at least two hydrogen atoms bonded to silicon atoms (hydrosilyl groups or SiH groups) in each molecule. For example, any of the various conventional organohydrogenpolysiloxanes having a linear, cyclic, branched, or three-dimensional network structure (resinous) structure can be used.
[0018] The organohydrogenpolysiloxane of component (B) has two or more, preferably three or more (usually about 3 to 500, preferably about 3 to 200, more preferably about 3 to 100) hydrogen atoms bonded to silicon atoms (hydrosilyl groups or SiH groups) per molecule. When the organohydrogenpolysiloxane of component (B) has a linear structure, these SiH groups may be located either at the molecular chain terminals or at non-terminal portions of the molecular chain, or may be located at both.
[0019] The number of silicon atoms in one molecule of component (B) (degree of polymerization) is preferably from 2 to 1,000, more preferably from 3 to 300, and even more preferably from about 4 to 150. Furthermore, the kinetic viscosity of component (B) at 25° C. is preferably from 10 to 100,000 mm 2 / s, and more preferably 20 to 50,000 mm 2 The kinematic viscosity of the organopolysiloxane of component (B) described in this specification is the value at 25°C measured with an Ostwald viscometer.
[0020] As the component (B), for example, an organohydrogenpolysiloxane represented by the following average composition formula (1) can be used. [ka] (In the formula, R 3 is an unsubstituted or substituted monovalent hydrocarbon group bonded to a silicon atom, excluding aliphatic unsaturated groups, preferably having 1 to 14 carbon atoms, more preferably 1 to 10 carbon atoms, and a and b are positive numbers that preferably satisfy 0.7≦a≦2.1, 0.001≦b≦1.0, and 0.8≦a+b≦3.0, more preferably 0.9≦a≦2.0, 0.01≦b≦1.0, and 1.0≦a+b≦2.5.
[0021] Above R 3Examples of the alkyl group include alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, neopentyl, hexyl, cyclohexyl, octyl, nonyl, and decyl; aryl groups such as phenyl, tolyl, xylyl, and naphthyl; aralkyl groups such as benzyl, phenylethyl, and phenylpropyl; and groups in which some or all of the hydrogen atoms in these hydrocarbon groups have been substituted with halogen atoms such as fluorine, bromine, and chlorine, for example, a chloromethyl group, a 3-chloropropyl group, a bromoethyl group, and a 3,3,3-trifluoropropyl group. Among these, preferred are alkyl groups and aryl groups, and more preferred are methyl and phenyl groups.
[0022] The component (B) can be obtained by a known method. A typical method for producing the component (B) is, for example, equilibrating 1,3,5,7-tetramethyl-1,3,5,7-tetrahydrocyclotetrasiloxane (or a mixture of the cyclotetrasiloxane and octamethylcyclotetrasiloxane in some cases) with a siloxane compound that is a terminal group source, such as hexamethyldisiloxane or 1,3-dihydro-1,1,3,3-tetramethyldisiloxane, or octamethylcyclotetrasiloxane with 1,3-dihydro-1,1,3,3-tetramethyldisiloxane, in the presence of a catalyst such as sulfuric acid, trifluoromethanesulfonic acid, or methanesulfonic acid, at a temperature of about -10 to +40°C.
[0023] Specific examples of component (B) include 1,1,3,3-tetramethyldisiloxane, 1,3,5,7-tetramethylcyclotetrasiloxane, tris(dimethylhydrogensiloxy)methylsilane, tris(dimethylhydrogensiloxy)phenylsilane, methylhydrogenpolysiloxane terminated at both molecular chain ends with trimethylsiloxy groups, dimethylsiloxane-methylhydrogensiloxane copolymer terminated at both molecular chain ends with trimethylsiloxy groups, dimethylsiloxane-methylhydrogensiloxane copolymer terminated at both molecular chain ends with trimethylsiloxy groups, and dimethylsiloxane-methylhydrogensiloxane copolymer terminated at both molecular chain ends with trimethylsiloxy groups. dimethylpolysiloxane-methylhydrogensiloxane-methylphenylsiloxane copolymer, dimethylpolysiloxane terminated at both molecular chain ends with dimethylhydrogensiloxy groups, dimethylpolysiloxane-methylhydrogensiloxane copolymer terminated at both molecular chain ends with dimethylhydrogensiloxy groups, dimethylsiloxane-methylphenylsiloxane copolymer terminated at both molecular chain ends with dimethylhydrogensiloxy groups, methylphenylpolysiloxane terminated at both molecular chain ends with dimethylhydrogensiloxy groups, formula: R 1 3SiO 0.5 (R 1 is as defined and exemplified for component (A). The same applies below.) and a siloxane unit represented by the formula: R 1 2HSiO 0.5 and an organopolysiloxane copolymer having a siloxane unit represented by the formula: SiO2, 1 2HSiO 0.5 and an organopolysiloxane copolymer having a siloxane unit represented by the formula: SiO2, 1 Siloxane unit represented by HSiO and formula: R 1 SiO 1.5 Siloxane unit or formula: HSiO 1.5 and organopolysiloxane copolymers comprising siloxane units represented by the following formula: These components (B) can be used singly or in combination of two or more.
[0024] The amount of the (B) component is such that the number of hydrogen atoms (SiH groups) bonded to silicon atoms in the (B) component per alkenyl group in the entire composition is in the range of 0.8 to 6, preferably 1.5 to 3.0. In this case, the ratio of the alkenyl groups bonded to silicon atoms in the (A) component to the alkenyl groups present in the entire composition is preferably 50 to 100 mol%, more preferably 80 to 100 mol%. When the (A) component is the only component having an alkenyl group in the entire composition, the amount of the (B) component SiH groups per alkenyl group bonded to silicon atoms in the (A) component is in the range of 0.5 to 10, preferably 1.0 to 8.0. If the amount of the (B) component is too small, the adhesion to the substrate may be poor, and if it is too large, the heat dissipation may be reduced.
[0025] (C) Component The hydrosilylation catalyst of component (C) may be any catalyst that promotes the addition reaction between the alkenyl group in component (A) and the SiH group in component (B). For example, platinum-based catalysts such as chloroplatinic acid, alcohol-modified chloroplatinic acid, and coordination compounds of chloroplatinic acid with olefins, vinylsiloxanes, or acetylene compounds; palladium-based catalysts such as tetrakis(triphenylphosphine)palladium; and rhodium-based catalysts such as chlorotris(triphenylphosphine)rhodium are used as component (C), with platinum-divinyltetramethyldisiloxane complexes being particularly preferred.
[0026] The amount of component (C) is not particularly limited as long as it is an effective amount as a hydrosilylation reaction catalyst, but is preferably 0.1 to 2,000 ppm, more preferably 1 to 1,500 ppm, by mass, calculated as the catalytic metal element relative to the total amount of components (A) and (B). When the amount added is within this range, the addition reaction is sufficiently promoted, the composition is sufficiently cured, and it is economically advantageous. In addition, the type of metal catalyst is not particularly limited as long as it is a metal that has effective activity as a hydrosilylation reaction catalyst, but platinum, which has the activity of splitting hydrogen gas into atoms, is useful.
[0027] (D) Component Component (D) has a tap density of 3.0 g / cm 3 and the specific surface area is 2.0m or more. 2 / g or less and an aspect ratio of 2.0 to 50.0. The tap density of the silver powder of component (D) is 3.0 g / cm 3 If it is smaller than this, the loading rate of component (D) in the composition cannot be increased, the viscosity of the composition increases, and workability deteriorates. Therefore, it is preferable that the loading rate is 3.0 g / cm. 3 ~10.0g / cm 3 The range is preferably 4.5 g / cm 3 ~10.0g / cm 3 More preferably, the range is 6.0 g / cm 3 ~10.0g / cm 3 The range is more preferred. The specific surface area of the silver powder in component (D) is 2.0 m 2 If the viscosity is greater than 0.08 m / g, the loading rate of component (D) in the composition cannot be increased, the viscosity of the composition increases, and workability deteriorates. 2 / g~2.0m 2 / g is preferred, and 0.08m 2 / g~1.0m 2 / g is more preferable, and 0.08m 2 / g~0.5m 2 / g range is more preferred. The tap density described in this specification is a value calculated from the volume of the compressed silver powder by weighing out 100 g of silver powder, gently dropping the silver powder into a 100 ml measuring cylinder using a funnel, placing the cylinder on a tap density meter and dropping it 600 times at a drop distance of 20 mm and a rate of 60 times per minute. The specific surface area was calculated by taking about 2 g of silver powder as a sample, degassing it for 10 minutes at 60±5℃, and then measuring the total surface area with an automatic specific surface area measuring device (DET method).Then, the sample amount was weighed and calculated using the following formula (2).
number
[0028] The aspect ratio of the silver powder of component (D) is 2.0 to 50.0, preferably in the range of 3.0 to 30.0, and more preferably in the range of 3.0 to 20.0. The aspect ratio refers to the ratio of the long diameter to the short diameter of a particle (long diameter / short diameter). For example, an electron microscope photograph of the particle is taken, and the long diameter and short diameter of the particle are measured from this photograph, and the aspect ratio can be calculated. The size of the particle can be measured from an electron microscope photograph taken from the top, and the larger diameter from this electron microscope photograph of the top is measured as the long diameter. The short diameter relative to this long diameter is the thickness of the particle. The thickness of the particle cannot be measured from an electron microscope photograph taken from the top. To measure the thickness of the particle, when taking an electron microscope photograph, the sample stage on which the particle is placed is tilted and attached, an electron microscope photograph is taken from the top, and the thickness of the particle is calculated by correcting for the angle of inclination of the sample stage. Specifically, several photographs were taken using an electron microscope at several thousand times magnification, and then the long and short diameters of 100 randomly selected particles were measured, the ratio of the long and short diameters (long diameter / short diameter) was calculated, and the average value was calculated to obtain the aspect ratio.
[0029] The particle size of the silver powder of component (D) is not particularly limited, but the average particle size is preferably in the range of 0.2 to 50 μm, and particularly preferably in the range of 1.0 to 30 μm. The average particle size described in this specification is the volume-based volume average diameter [MV] measured by a laser diffraction particle size analyzer after placing 1 to 2 scoops of silver powder in a 100 ml beaker with a micro spatula, adding about 60 ml of isopropyl alcohol, and dispersing the silver powder with an ultrasonic homogenizer for 1 minute. The measurement time was 30 seconds.
[0030] The method for producing the silver powder used in the present invention is not particularly limited, but silver powder produced by a reduction method is preferred. The silver powder produced by the above method may be used as it is, or may be pulverized to a range satisfying the above numerical range. When pulverizing the silver powder, the apparatus is not particularly limited, and for example, known apparatus such as a stamp mill, a ball mill, a vibration mill, a hammer mill, a rolling roller, a mortar, etc. can be used. Among them, a stamp mill, a ball mill, a vibration mill, and a hammer mill are preferable.
[0031] The blending amount of the (D) component is 500 to 3,000 parts by mass per 100 parts by mass of the (A) component. If the blending amount of the (D) component is less than 500 parts by mass per 100 parts by mass of the (A) component, the thermal conductivity of the cured product of the obtained composition will be poor, and if it is more than 3,000 parts by mass, the fluidity of the composition will be poor and the handling of the composition will be poor. The blending amount of the (D) component is preferably in the range of 600 to 2,000 parts by mass, more preferably 700 to 1,500 parts by mass per 100 parts by mass of the (A) component.
[0032] (E) Component Component (E) has an average particle size of 0.5 to 100 μm and a tap density of 4.0 g / cm 3 and the specific surface area is 1.5m or more. 2 / g or less and has an aspect ratio of less than 2.0. If the average particle size of the spherical silver powder of component (E) is less than 0.5 μm, the thermal conductivity of the cured product of the obtained composition will be poor.If it is more than 100 μm, it will be difficult to form a heat path in the cured product of the obtained composition, and the thermal conductivity will be poor. Therefore, the average particle size is preferably 1.0 to 50 μm, more preferably 2.0 to 10 μm.
[0033] The tap density of the spherical silver powder of component (E) is 4.0 g / cm 3 If it is smaller than this, the loading rate of component (E) in the composition cannot be increased, the viscosity of the composition increases, and workability deteriorates. Therefore, it is preferable that the loading rate is 4.0 g / cm. 3 ~10.0g / cm 3 The range is preferably 4.5 g / cm 3 ~10.0g / cm 3 More preferably, the range is 6.0 g / cm 3 ~10.0g / cm 3 The range is more preferred. The specific surface area of the spherical silver powder of component (E) is 1.5 m 2 If it is greater than 0.08 m / g, the loading rate of the component (E) in the composition cannot be increased, the viscosity of the composition increases, and workability deteriorates. 2 / g~1.5m 2 / g is preferred, and 0.08m 2 / g~1.0m 2 / g is more preferable, and 0.08m 2 / g~0.5m 2 / g range is more preferred. The aspect ratio of the spherical silver powder of component (E) is less than 2.0, preferably 1.5 or less, and more preferably 1.2 or less. Here, the aspect ratio refers to the ratio of the major axis to the minor axis of a particle (major axis / minor axis). The measurement method is the same as that described above.
[0034] The method for producing the spherical silver powder of component (E) is not particularly limited, but an atomization method is preferred.
[0035] The blending amount of the (E) component is 500 to 3,000 parts by mass per 100 parts by mass of the (A) component. If the blending amount of the (E) component is less than 500 parts by mass per 100 parts by mass of the (A) component, the thermal conductivity of the cured product of the obtained composition will be poor, and if it is more than 3,000 parts by mass, the fluidity of the composition will be poor and handling will be poor. The blending amount of the (E) component is preferably 600 to 2,000 parts by mass, more preferably 700 to 1,500 parts by mass per 100 parts by mass of the (A) component.
[0036] The ratio α / β, which is the mass α of the component (D) to the mass β of the component (E), is preferably in the range of 0.1 to 6, more preferably in the range of 0.2 to 5.5, even more preferably in the range of 0.5 to 5, and most preferably in the range of 0.8 to 4. If it is in such a range, the thermal conductivity of the cured product of the obtained composition will be superior.
[0037] Other Ingredients The thermally conductive silicone composition of the present invention may contain the following optional components in addition to the above components (A) to (E).
[0038] Curing reaction control agent The composition of the present invention may use a curing reaction control agent having a curing inhibitory effect against addition reaction catalysts. Examples of such compounds include phosphorus-containing compounds (such as triphenylphosphine), nitrogen-containing compounds (such as tributylamine, tetramethylethylenediamine, and benzotriazole), sulfur-containing compounds, acetylene-based compounds (such as 1-ethynyl-1-cyclohexanol), triallyl isocyanuric acid, hydroperoxy compounds, and maleic acid derivatives. The degree of the curing retardation effect of the curing reaction control agent varies greatly depending on the chemical structure of the curing reaction control agent. Therefore, the amount of the curing reaction control agent to be added should be adjusted to an optimal amount for each curing reaction control agent used, but such adjustment can be easily performed by a method well known to those skilled in the art. When the curing reaction control agent is added to the composition of the present invention, the composition of the present invention can be stored for a long time at room temperature, but if the amount of the curing reaction control agent added is too large, the curing of the composition may be inhibited.
[0039] Inorganic compound powders and / or organic compound materials other than components (D) and (E) Examples of inorganic compound powders and / or organic compound materials other than the (D) component and the (E) component include metal powders such as aluminum, gold, copper, nickel, indium, gallium, palladium, and silicon metal; diamond powder; carbon materials such as carbon fiber, graphene, graphite, carbon nanotubes, and carbon black; metal oxide powders such as zinc oxide, titanium oxide, magnesium oxide, alumina, iron oxide, and silicon dioxide (fumed silica, crystalline silica, precipitated silica, and the like); metal hydroxide powders such as aluminum hydroxide; nitride powders such as boron nitride and aluminum nitride; carbonates such as magnesium carbonate, calcium carbonate, and zinc carbonate; hollow fillers; silsesquioxane; layered mica; diatomaceous earth; glass fiber; silicone rubber powder; and silicone resin powder. Among these, those with high thermal conductivity are preferred. Examples of inorganic compound powders and / or organic compound materials with high thermal conductivity include aluminum powder, zinc oxide powder, titanium oxide powder, magnesium oxide powder, alumina powder, aluminum hydroxide powder, boron nitride powder, aluminum nitride powder, diamond powder, gold powder, copper powder, carbon powder, nickel powder, indium powder, gallium powder, metal silicon powder, silicon dioxide powder, carbon fiber, graphene, graphite, and carbon nanotubes. These may be used alone or in combination of two or more.
[0040] The surfaces of these inorganic compound powders and organic compound materials may be hydrophobized with organosilane, organosilazane, organopolysiloxane, organic fluorine compounds, etc., if necessary. The average particle size of the inorganic compound powder and the organic compound material is preferably in the range of 0.5 to 100 μm, and more preferably in the range of 1 to 50 μm, since the filling rate in the obtained composition does not increase if it is smaller than 0.5 μm or larger than 100 μm. The fiber length of the carbon fiber is preferably in the range of 10 to 500 μm, and more preferably in the range of 30 to 300 μm, since the filling rate in the obtained composition does not increase if it is smaller than 10 μm or larger than 500 μm.
[0041] If the total amount of the inorganic compound powder and the organic compound material exceeds 3,000 parts by mass per 100 parts by mass of component (A), the fluidity of the composition deteriorates and the handleability of the composition deteriorates. Therefore, the total amount is preferably 0.1 to 3,000 parts by mass, and more preferably 1 to 2,000 parts by mass.
[0042] Furthermore, the composition of the present invention may contain other optional components, such as organopolysiloxanes containing one hydrogen atom or one alkenyl group bonded to a silicon atom in each molecule, organopolysiloxanes containing neither a hydrogen atom bonded to a silicon atom nor an alkenyl group, organic solvents, agents imparting heat resistance, agents imparting flame retardancy, plasticizers, agents imparting thixotropy, dyes, and mildew inhibitors, provided such components do not impair the object of the present invention.
[0043] Manufacturing method The method for producing the thermally conductive silicone composition of the present invention may be according to the conventional method for producing silicone compositions, and is not particularly limited. For example, the above components (A) to (E) and other components as necessary can be mixed for 10 minutes to 4 hours using a mixer such as Trimix, Twinmix, Planetary Mixer (all mixers manufactured by Inoue Seisakusho Co., Ltd., registered trademark), Ultra Mixer (mixer manufactured by Mizuho Kogyo Co., Ltd., registered trademark), or Hivis Dispermix (mixer manufactured by Primix Co., Ltd., registered trademark). If necessary, the mixture may be mixed while heating at a temperature in the range of 30 to 200°C.
[0044] The thermally conductive silicone composition of the present invention preferably has an absolute viscosity measured at 25°C of 10 to 1,000 Pa·s, more preferably 50 to 700 Pa·s, and even more preferably 80 to 600 Pa·s. When the absolute viscosity is within the above range, a good grease can be provided, and workability is also excellent. The absolute viscosity can be obtained by adjusting the blending amounts of each component as described above. The absolute viscosity can be measured, for example, using a model PC-1TL (10 rpm) manufactured by Malcom Co., Ltd.
[0045] The thermally conductive silicone composition of the present invention is cured by heating the thermally conductive silicone composition obtained as described above to a temperature of 80° C. or higher under a pressure of 0.01 MPa or more. There are no limitations on the properties of the cured product thus obtained, but examples of the cured product include a gel, a low hardness rubber, or a high hardness rubber.
[0046] Semiconductor Device The semiconductor device of the present invention is characterized in that a cured product of the thermally conductive silicone composition of the present invention is interposed between the surface of a heat-generating electronic component and a heat sink. The cured product of the thermally conductive silicone composition of the present invention is preferably interposed at a thickness of 10 to 200 μm. A typical structure is shown in Fig. 1, but the present invention is not limited to this. Fig. 1 is a schematic vertical cross-sectional view showing an example of a semiconductor device of the present invention, and for example, the semiconductor device of the present invention has a heat-generating electronic component (CPU) 2 mounted on a substrate 1 and a heat sink (lid) 4, with a thermally conductive silicone composition layer 3 interposed between them, and the thermally conductive silicone composition layer 3 is a cured product of the thermally conductive silicone composition of the present invention.
[0047] A preferred method for producing the semiconductor device of the present invention is to heat the thermally conductive silicone composition of the present invention to 80°C or higher while applying a pressure of 0.01 MPa or more between a heat-generating electronic component and a heat sink. In this case, the pressure applied is preferably 0.01 MPa or more, particularly preferably 0.05 MPa to 100 MPa, and more preferably 0.1 MPa to 100 MPa. The heating temperature must be 80°C or higher, preferably 100°C to 300°C, more preferably 120°C to 300°C, and even more preferably 140°C to 300°C. EXAMPLES
[0048] In the following, the present invention will be described in more detail with reference to examples and comparative examples in order to clarify the effects of the present invention, but the present invention is not limited thereto. The kinetic viscosities of components (A) and (B) are values measured at 25°C using an Ostwald viscometer. The components used in the examples and comparative examples are shown below.
[0049] Component (A) A-1: Both ends are blocked with dimethylvinylsilyl groups, and the kinetic viscosity at 25°C is 600mm 2 / s Dimethylpolysiloxane
[0050] (B) Component B-1: Organohydrogenpolysiloxane represented by the following formula (having a kinetic viscosity of 30 mm at 25°C) 2 / s) [ka]
[0051] (C) Component C-1 (Platinum catalyst): A-1 solution of platinum-divinyltetramethyldisiloxane complex, containing 1 wt% platinum atoms
[0052] (D) Component D-1: Tap density is 5.5g / cm 3 , specific surface area is 0.8m 2 / g, aspect ratio 8.0, average particle size 2μm silver powder D-2: Tap density is 6.2g / cm 3 , specific surface area is 0.5m 2 / g, aspect ratio 13.0, average particle size 4μm silver powder D-3: Tap density is 9.0g / cm 3 , specific surface area is 0.2m 2 / g, aspect ratio 30.0, average particle size 10μm silver powder D-4: Tap density is 3.0g / cm 3 , specific surface area is 2.0m 2 / g, aspect ratio 47.0, average particle size 14μm silver powder D-5 (comparison example): Tap density is 2.3 g / cm 3 , specific surface area is 1.8m 2 / g, aspect ratio 3.0, average particle size 1μm silver powder D-6 (Comparative Example): Tap density is 3.3 g / cm 3 , specific surface area is 3.0m 2 / g, aspect ratio 4.0, average particle size 0.1μm silver powder
[0053] (E) Component E-1: Average particle size 3 μm, tap density 6.5 g / cm 3 , specific surface area is 0.3m 2 / g, spherical silver powder with an aspect ratio of 1.2 E-2: Average particle size 0.8 μm, tap density 4.3 g / cm 3 , specific surface area is 1.2m 2 / g, spherical silver powder with an aspect ratio of 1.5 E-3: Average particle size 70 μm, tap density 6.0 g / cm 3, specific surface area is 0.2m 2 / g, spherical silver powder with an aspect ratio of 1.1 E-4 (Comparative Example): Average particle size 0.3 μm, tap density 3.8 g / cm 3 , specific surface area is 2.2m 2 / g, spherical silver powder with an aspect ratio of 1.6 E-5 (Comparative Example): Average particle size 105 μm, tap density 5.0 g / cm 3 , specific surface area is 0.5m 2 / g, spherical silver powder with an aspect ratio of 1.8
[0054] (F) Component: Curing reaction regulator F-1: 1-ethynyl-1-cyclohexanol
[0055] [Examples 1 to 9 and Comparative Examples 1 to 8] The compositions of Examples 1 to 9 and Comparative Examples 1 to 8 were obtained by mixing the components in the following compositions shown in Tables 1 and 2 (the numerical values for each component are in parts by mass) as follows. That is, components (A), (D), and (E) were placed in a 5-liter planetary mixer (manufactured by Inoue Seisakusho Co., Ltd.) and mixed for 1.5 hours at 25° C. Next, components (C) and (F) were added and mixed for 15 minutes at 25° C. Finally, component (B) was added and mixed until uniform.
[0056] 〔viscosity〕 The absolute viscosity of each composition was measured at 25° C. using a Malcolm viscometer (type PC-1TL).
[0057] [Thermal resistance] Each composition was sandwiched between two φ12.7mm aluminum plates, and heated and cured in a 150°C oven for 90 minutes under a pressure of 0.35MPa. Three types of test pieces were prepared, with minimum thickness (BLT), 75μm, and 100μm, depending on the presence or absence of a spacer when sandwiching the composition and the difference in thickness (no spacer, 75μm, 100μm), and the thermal resistance of each was measured at 25°C using Nanoflash (Nitsche, LFA447). The BLT was measured using a Digimatic Standard Outside Micrometer (Mitutoyo, MDC-25MX) and calculated using the following formula (3).
number
[0058] [Table 1]
[0059] [Table 2]
[0060] As shown in Table 1, the cured product of the thermally conductive silicone composition had sufficiently low thermal resistance even when it was thicker than the minimum thickness when compressed (BLT). On the other hand, as shown in Table 2, in Comparative Example 1, in which the blending amounts of the (D) component and the (E) component were small, the thermal resistance was large and the desired thermal performance was not obtained. In Comparative Example 2, in which the blending amounts of the (D) component and the (E) component were large, the composition did not become grease-like and was poor in handleability. In Comparative Example 3, in which the average particle size of the (E) component was small, the thermal resistance was large when the thickness was large, and in Comparative Example 4, in which the average particle size of the (E) component was large, the thermal resistance was large and the thermal resistance when the thickness was large was not measurable. In Comparative Examples 5 and 6, in which silver powders whose tap density or specific surface area did not satisfy the range of the (D) component in the present invention were used, the viscosity of the obtained composition was high and the thermal resistance was also high. In Comparative Examples 7 and 8, in which the blending amounts of one of the (D) component and the (E) component were small, the thermal resistance when the thickness was large was large. [Explanation of symbols]
[0061] 1. Substrate 2. Heat-generating electronic components (CPU) 3. Thermally conductive silicone composition layer 4. Heat sink (lid)
Claims
1. A thermally conductive silicone composition comprising the following components (A), (B), (C), (D), and (E): (A) A kinematic viscosity at 25°C of 10 to 100,000 mm 2 / s, and containing at least two alkenyl groups bonded to silicon atoms in each molecule: 100 parts by mass (B) Organohydrogenpolysiloxane containing at least two hydrogen atoms bonded to silicon atoms (SiH groups) per molecule: an amount such that the number of hydrogen atoms bonded to silicon atoms in component (B) is 0.8 to 6 per alkenyl group in the entire composition (C) Hydrosilylation reaction catalyst: effective amount (D) Tap density is 3.0 g / cm 3 or more, and the specific surface area is 2.0 m 2 / g or less and an aspect ratio of 2.0 to 50: 500 to 3,000 parts by mass (E) The average particle size is 0.5 to 100 μm and the tap density is 4.0 g / cm 3 The specific surface area is 1.5 m or more. 2 / g or less and an aspect ratio of less than 2.0: 500 to 3,000 parts by mass
2. 2. The thermally conductive silicone composition according to claim 1, wherein the ratio α / β, where α is the mass of component (D) to β is the mass of component (E), is 0.1 to 6.
3. A cured product of the thermally conductive silicone composition according to claim 1 or 2.
4. 4. A semiconductor device comprising a heat-generating electronic component and a heat sink, wherein a cured product of the thermally conductive silicone composition according to claim 3 is interposed between the heat-generating electronic component and the heat sink.
5. 3. A method for manufacturing a semiconductor device, comprising the step of heating the thermally conductive silicone composition according to claim 1 or 2 to 80° C. or higher while applying a pressure of 0.01 MPa or more between a heat-generating electronic component and a heat sink.
Citation Information
Patent Citations
Silicone grease composition
JP1990153995A
Thermally conductive organo- siloxane compounds
JP1991014873A
Thermoconductive silicone composition, thermoconductive material and thermoconductive silicone grease
JP1998110179A
Heat conductive grease composition
JP2000063872A
Heat conductive grease composition and semiconductor device using same
JP2000063873A